2017
DOI: 10.1111/liv.13487
|View full text |Cite
|
Sign up to set email alerts
|

New intermediate‐stage subclassification for patients with hepatocellular carcinoma treated with transarterial chemoembolization

Abstract: Our new BCLC B substaging system, with up-to-11 criteria and Child-Pugh class as main parameters, has excellent discriminatory power to subclassify TACE-treated patients into three prognostic substages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 20 publications
(64 reference statements)
2
85
0
Order By: Relevance
“…Kaplan–Meier analysis showed that the HAP model also significantly discriminated OS across HAP class A to D in the training and validation cohorts and the overall patients ( P < .001, Figure D‐F). The discriminatory ability of the ALBI‐TAE model was further compared to the HAP model, BCLC‐B subclassification and another recently reported new BCLC‐B subclassification using both the training and validation datasets as well as the overall cohort using AUROC curve, AICc and homogeneity. As shown in Table , the ALBI‐TAE model offered the lowest AICc values and highest homogeneity in both the training and validation datasets as well as the overall cohort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaplan–Meier analysis showed that the HAP model also significantly discriminated OS across HAP class A to D in the training and validation cohorts and the overall patients ( P < .001, Figure D‐F). The discriminatory ability of the ALBI‐TAE model was further compared to the HAP model, BCLC‐B subclassification and another recently reported new BCLC‐B subclassification using both the training and validation datasets as well as the overall cohort using AUROC curve, AICc and homogeneity. As shown in Table , the ALBI‐TAE model offered the lowest AICc values and highest homogeneity in both the training and validation datasets as well as the overall cohort.…”
Section: Resultsmentioning
confidence: 99%
“…The AST to Platelet Ratio Index (APRI) was calculated using the formula: ([AST/upper limit of normal]/platelet count [10 9 /L]) × 100 . The Up‐to‐7 criteria combined the number of tumours and size of the largest tumour, with the sum being no more than 7, whereas the up‐to‐11 criteria combined the number of tumours and size of the largest tumour, with the sum being no more than 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent evaluation of the prognostic capability of the subclassification of Bolondi et al [16] has been carried out by Kim et al [23] on 821 patients treated with TACE. The B1, B2 and B3 subclasses showed significantly different survival rates between the contiguous stages with a median survival of 51.5, 26, and 14.8 months, respectively (p < 0.001 for each comparison with the contiguous stratum until B3); however, the discriminatory ability and the gradient monotonicity of the system disappeared between B3 and B4 since the median survival of B3 was worse than that of B4 patients (14.8 vs. 25 months, p = 0.025).…”
mentioning
confidence: 99%
“…In an attempt to estimate the potential applicability of these subclassifications in clinical practice, it should be noted that two of them [16,23] In the ECOG scale, PS 1 refers to patients not being able to engage in strenuous physical activity but being ambulatory and able to carry out work of a light or sedentary nature, such as light housework or office work. Therefore, PS 1 does not preclude access to any type of HCC treatment and, consequently, the Italian guidelines for the management of HCC patients have not accepted the exclusion of these patients from the BCLC B stage (or its substages) [30].…”
mentioning
confidence: 99%